Highland barley arabinoxylans with distinct molecular features modulate retrogradation and in vitro digestibility of highland barley starch - Yonghui Dong; Tingting Mu; Xue Wu; Chunping Chen; Haiyu Wu; Lin Han; Caian He; Min Wang (Food Hydrocolloids, 2026)

CCT7 predicts poor prognosis and correlates with immune infiltration in colonic adenocarcinoma - Wenxu Li; Qizhong Shi; Yonghui Mu; Chenglei Li; Wenchao Zhao; Na Han (Journal of Molecular Histology, 2026)
CCT7, a member of the t-complex polypeptide 1 chaperone family, facilitates ATP-dependent protein folding; however, its role in development and progression of malignant tumors remains unclear. This study aimed to characterize the expression pattern of CCT7 in colonic adenocarcinoma (COAD) and evaluate its role in the initiation and development of COAD. Public bioinformatic databases were analyzed to assess CCT7 expression in COAD, and these findings were validated using human clinical specimens through immunohistochemistry (IHC) assay. The prognostic significance of CCT7 was examined using Kaplan–Meier method and Cox regression analysis. Gene Ontology-Biological Process (GO-BP) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to explore the potential biological functions and downstream pathways associated with CCT7. CCK-8, colony formation and Transwell assays were conducted to determine the impact of CCT7 on cell proliferation, migration and invasion in COAD cell lines. Associations between CCT7 expression and immune cell infiltration or drug sensitivity were evaluated using single-sample gene set enrichment analysis and correlation analysis. Finally, immune checkpoint inhibitor therapy scores and their relationship with CCT7 expression were assessed using data from The Cancer Immunome Atlas. CCT7 expression was significantly up-regulated statistically in COAD tissues compared with normal colonic tissues ( P < 0.05) and elevated CCT7 levels were associated with poorer prognosis of COAD patients ( P < 0.05). GO-BP enrichment analysis indicated that CCT7 was primarily involved in the processes related to cell proliferation and microtubule organization ( P < 0.05). Consistently, functional assays confirmed that CCT7 knockdown inhibited COAD cell proliferation, migration, and invasion ( P < 0.05). CCT7 expression showed a negative correlation with infiltration of most immune cell types ( P < 0.05) and demonstrated no significant association with predicted responses to PD-1 and CTLA-4 inhibitor therapies ( P > 0.05). Moreover, drug sensitivity analyses showed that CCT7 affected the sensitivity of COAD samples to several anti-cancer drugs ( P < 0.001). KEGG enrichment analysis revealed that CCT7 was associated with multiple pathways ( P < 0.05). CCT7 may function as an oncogenic driver that promotes the malignant phenotype of COAD and represents a promising prognostic biomarker. It may also provide a valuable reference for guiding clinical therapeutic strategies in COAD.

Entropy engineering in metavalent-bonded SnTe for high thermoelectric performance - Yaning Wang; Yi Yuan; Yonghui Ma; Guojian Li; Tie Liu; Wangzhong Mu; Qiang Wang (Chemical Engineering Journal, 2025)

Single-atom nanozyme immunoassay with electron-rich property for clinical patient cancer detection - Qingshan Liu; Guo Li; Yang Cao; Yaoyao Ren; Qiong Qin; Lei Li; Hao Zhang; Qi Xin; Xiaoqun Gong; Lingyu Zhao; Shu Zhang; Yonghui Li; et al. (Chemical Engineering Journal, 2025)

Influence of solar radiation on the surface loss of the painted statues in Grotto No. 3 of Maijishan Grottoes, China - Ruobin Wu; Yan Ma; Huarong Xie; Xudong Wang; Shuichi Hokoi; Yongqiang Yue; Junjian Hu; Baogang Mu; Yonghui Li (Building and Environment, 2023)

Genetic variation and phylogenetic analysis of porcine circovirus type 2 infections in central China - Chunlong Mu; Qingyuan Yang; Yina Zhang; Yonghui Zhou; Jixi Zhang; Darren P. Martin; Pingan Xia; Baoan Cui (Virus Genes, 2012)

A study on the nonlinear stability of fronts in the ocean on a sloping continental shelf - Li Yang; Mu Mu; Wu Yonghui (Advances in Atmospheric Sciences, 2000)

Nonlinear stability analysis of the zonal flows at middle and high latitudes - Mu Mu; Wu Yonghui; Liu Haiyan; Tang Mozhi (Advances in Atmospheric Sciences, 1999)